Suppression of MicroRNA 200 Family Expression by Oncogenic KRAS Activation Promotes Cell Survival and Epithelial-Mesenchymal Transition in KRAS-Driven Cancer - Zhong, Xiaomin; Zheng, Lan; Shen, Jianfeng; Zhang, Dongmei; Xiong, Minmin; Zhang, Youyou; He, Xinhong; Tanyi, Janos L.; Yang, Feng; Montone, Kathleen T.; Chen, Xiaojun; Xu, Congjian; et al. (Molecular and cellular biology, 2016)
Oncogenic KRAS contributes to malignant transformation, antiapoptosis, and metastasis in multiple human cancers, such as lung, colon, and pancreatic cancers and melanoma. MicroRNAs (miRNAs) are endogenous 18- to 25-nucleotide noncoding small RNAs that regulate gene expression in a sequence-specific manner via the degradation of target mRNAs or inhibition of protein translation. In the present study, using array-based miRNA profiling in IMR90 and MCF10A cells expressing oncogenic KRAS, we identified that the expression of the microRNA 200 (mir-200) family was suppressed by KRAS activation and that this suppression was mediated by the transcription factors JUN and SP1 in addition to ZEB1. Restoration of mir-200 expression compromised KRAS-induced cellular transformation in vitro and tumor formation in vivo. In addition, we found that enforced expression of mir-200 abrogated KRAS-induced resistance to apoptosis by directly targeting the antiapoptotic gene BCL2. Finally, mir-200 was able to antagonize the epithelial-mesenchymal transition (EMT) driven by mutant KRAS. Collectively, our results suggest that repression of endogenous mir-200 expression is one of the important cellular responses to KRAS activation during tumor initiation and progression.